Chlorination by-products in tap water and semen quality in England and Wales. Issue 11 (12th June 2013) - Iszatt, Nina; Nieuwenhuijsen, Mark J; Bennett, James; Best, Nicky; Povey, Andrew C; Pacey, Allan A; Moore, Harry; Cherry, Nicola; Toledano, Mireille B
Abstract : Objectives: Disinfection by-products (DBPs) have been associated with adverse semen outcomes in laboratory animals, although the evidence for trihalomethanes (THMs) is limited. Three small epidemiological studies found little evidence for an association between DBPs and adverse semen outcomes in humans. Using data from a large case–referent study (Chemicals and Pregnancy Study, Chaps-UK), we investigated the association between total THM (TTHM), chloroform and total brominated THMs and sperm concentration, percent motile sperm and motile sperm concentration (MSC). Methods: Chaps-UK recruited men from 13 fertility clinics in nine urban centres across England and Wales between 1999 and 2002. We linked modelled THM concentrations in water zones to semen quality data for 642 cases (men with low MSC) and 926 referents (other men investigated for infertility), based on the men's residence during semen sampling. We assessed risk of low MSC in relation to DBP exposure using continuous THM concentrations. A secondary analysis investigated continuous outcomes (MSC, sperm concentration and percent motile sperm). Results: In the case–referent analysis there was little evidence of elevated risk associated with chloroform, total brominated THM or TTHM concentration after adjustment (OR per 10 µg/L TTHM 1.01; 95% CI 0.91 to 1.12). Similarly, there was no significant effect of THMs on the continuous outcomes. Conclusions: In the largest study to date on DBPs in public water supplies, and semen quality we found that concentrations of THMs were not associated with poor semen quality. Large-scale investigation of other DBPs (eg, haloacetic acids) and other semen quality parameters (eg, sperm morphology and/or sperm DNA integrity) is recommended.